Increased Direct Current-Electroencephalography Shifts During Induction of Anesthesia in Elderly Patients Developing Postoperative Delirium - Windmann, Victoria; Dreier, Jens P.; Major, Sebastian; Spies, Claudia; Lachmann, Gunnar; Koch, Susanne (Frontiers in Aging Neuroscience, 2022)
Background: Changes in the direct current (DC) electroencephalography (EEG), so-called DC shifts, are observed during hypoxia, hypo-/hypercapnia, anesthetic administration, epileptic seizures and spreading depolarizations. They are associated with altered cerebral ion currents across cell membranes and/or the blood-brain barrier (BBB). Here, we measured DC shifts in clinical practice during hyperventilation (HV) and anesthesia induction, and investigated whether such DC shifts correlate with the occurrence of postoperative delirium (POD) in older patients. Methods: In this prospective observational study (subproject of the BioCog study, NCT02265263; EA2/092/14), a continuous pre- and perioperative DC-EEG was recorded in patients aged ≥ 65 years. The preoperative DC-EEG included a 2 minute HV with simultaneous measurement of end-tidal CO2. Of the perioperative recordings, DC-EEG segments were chosen from a 30s period at the start of induction of anesthesia (IOA), loss of consciousness (LOC), and during a stable anesthetic phase 30 min after skin incision (intraOP). The DC shift at Cz was determined in µV/s. All patients were screened twice daily for the first 7 postoperative days for the occurrence of postoperative delirium. DC-EEG shifts were compared in patients with (POD) and without postoperative delirium (noPOD). Results: Fifteen patients were included in this subproject of the BioCog study. DC shifts correlated significantly with concurrent HV, with DC shifts increasing the more end-tidal CO2 decreased (p=0.001, Spearman’s Rho 0.862). During the perioperative DC-EEG, the largest DC shift was observed at LOC during induction of anesthesia. POD patients (n=8) presented with significantly larger DC shifts at LOC (POD 31.6 [22.7; 38.9] µV/s vs. noPOD 4.7 [2.2; 12.5] µV/s, p=0.026). Conclusions: DC shifts can be observed during HV and induction of anesthesia in routine clinical practice. At anesthesia induction, the DC shift was greatest at the time of LOC, with POD patients presenting with significantly stronger DC shifts. This could indicate larger changes in gas tensions, hypotension and impaired cerebral autoregulation or BBB dysfunction in these patients.